Synthesis and characterization of L-threonine lithium chloride (LTLC): A new semiorganic nonlinear optical single crystal for laser applications. (2021) - Indumathi, N.; Hemalatha, A.; Chinnasamy, E.; Venkatesan, A.; Raja Saravanan, M.E.; Deepa, K.; Matheswaran, P.; Senthil, S.; Kaviyarasu, K.; Uthrakumar, R.
Abstract: A novel new nonlinear optical material of semi organic L-Threonine Lithium chloride (LTLC) was synthesized and crystal-clear single crystal was grown by slow evaporation solution growth technique at the ambient temperature. The grown transparent single crystal was characterized by single crystal X-ray diffraction (SCXRD), optical absorption spectrum, Fourier transforms infrared spectroscopy and Fourier transforms Raman spectroscopy. Single crystal X-ray diffraction analysis reveals that LTLC is an orthorhombic crystal structure with the non-centrosymmetric of P21 21 21 space group. The absorption range was evaluated from UV–vis-NIR and the optical band gap was calculated by Tauc's plot and Photoluminescent spectra were obtained to investigate the optical properties. The dielectric response was studied under various temperatures. The second harmonic generation (SHG) efficiency was studied by Kurtz Perry method.